EFEKTIVITAS MEDIA VIDEO ANIMASI UNTUK PEMBELAJARAN PEMANASAN GLOBAL PADA SISWA SMP - Arianti, Ratiwi; Indrawati, Indrawati; Wicaksono, Iwan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to examine the effectiveness of video animation media on global warming material t. This type of research is a quantitative descriptive study with a One Group Pretest-Posttest design. This research was conducted at Junior High School 3 Lumajang. The research subjects were students of 7th Â grade of Junior High School 3 Lumajang. Data collection techniques in this study were observation to observe student activities, questionnaires for student responses and pretest-posttest to improve learning outcomes. The data analysis technique uses percentages for activity and response analysis, while for improving learning outcomes using the n-gain test. The results show that student activity is obtained on average 70.834% with sufficient categories, student responses obtained on average 76.25% with good categories , the increase in learning outcomes obtained an average n-gain value of 0.745 with a high classification. So learning global warming material using animated video media is said to be effective.